Maturation of Radiocephalic Arteriovenous Fistula with and without Hydro dilatation: A Study on the Diameter and Flow Volume of the Draining Vein - Eko Dion Pandin Purba Sigoemondrong; Patrianef Darwis; Dian Kusumadewi (Eduvest - Journal of Universal Studies, 2026)
Radiocephalic arteriovenous fistula (AVF-RC) is the primary vascular access in patients with end-stage chronic kidney disease undergoing hemodialysis. One of the main challenges of using AVF-RC is the failure of early maturation, characterized by inadequate diameter and flow volume of the draining vein. Hydro dilatation is a simple intraoperative technique that aims to increase the distensibility and diameter of the veins, so that it is expected to accelerate the maturation process of the fistula. This study used a retrospective cohort design involving patients with chronic kidney disease who were undergoing hemodialysis and had AVF-RC created for the first time at Yarsi Hospital between October 2023 and September 2025. Subjects were divided into two groups, namely the group with and without hydro dilatation, with 60 patients in each group. A total of 120 patients were analyzed, with a median age of 54 years, and the majority were male. The diameter of the draining vein increased significantly from preoperative to 6 weeks postoperative in all patients (p < 0.001). The increase in draining vein diameter at weeks 1 and 6 postoperatively was significantly greater in the hydro dilatation group than in the non-hydro dilatation group (p < 0.001). Hydro dilatation has a significant effect on increasing the diameter and flow volume of the draining vein of AVF-RC, particularly in the early period of maturation. This technique has the potential to improve the success of AVF maturation and can be considered as part of an intraoperative strategy for optimizing vascular access for hemodialysis.